Russia in the context of Eurasian integration: The social dimension - G I Osadchaya (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2015)
On the basis of empirical data (a number of representative nationwide opinion polls and expert estimates) the article presented a detailed overview of the Russians’ and experts’ perception of the results and prospects of the Eurasian integration, and an analytical evaluation of their opinions, hopes and expectations taking into account the potential of the labor movement in the new integrated socio-economic and geopolitical space. The author explains the role and meaning of the social interaction of members of the Eurasian Economic Union (EEU) in ensuring the effectiveness of integration, and proposes methodological foundations for the development of the social model of the Eurasian Union with an emphasis on its social dimension. The article reveals the essence of the today supranational model of social policy and its influence on social policies of the members of EEU. Thus, the author explains the primary need to harmonize social actions of the members of EEU in employment policies, and proposes a number of measures for social policy in Russia to ensure free movement of labor in the Eurasian economic space as a key host state and society.